Caracterización de las organizaciones de la Economía Popular y Solidaria en la Parroquia San Lucas, Cantón Loja - Gualán Lozano, Silvia Nathaly (2018)
The Banking and Finance Career has been running since 2017 the project of investigation called "Forms of Cooperation that coexist within the framework of the Popular and Solidarity Economy in the rural parishes of the Loja Canton" the same as consisted in characterizing, diagnosing and evaluating the different organizations belonging to the thirteen parishes. As part of the aforementioned project, the present thesis was carried out, whose general objective was to evaluate the forms of cooperation and solidarity that coexist within the framework of the Popular and Solidarity Economy in the study zone. To comply a first specific objective, the bibliographic, deductive method and the direct observation form were used, through which the relevant aspects of the parish were characterized, such as: demography, social development and productive economic development. The second objective was focused on making a diagnosis of the intervention of the entities or financial organizations of the Popular and Solidarity Economy and measuring its impact, in order to verify whether the financial organizations really influence the economic and social development of their beneficiaries and therefore of the parish through the products and services they provide. Through the deductive method and the technique of direct observation, the problems and needs that arise in the parish were determined. In order to solve this, a proposal for integration and training was designed, with the aim of boosting the development of the sector. It is concluded that the intervention of the forms of cooperation of the Popular and Solidarity Economy is a fundamental pillar for the social and economic development of the San Lucas Parish, since the level of contribution that these have provided is high, since with the formation of organizations financial institutions the population had greater facility to finance their small ventures.